Theoretical Aspects Of Career Patterns Under The Organization And Individual Career Management Perspectives - Visi, Olgerta (European Scientific Journal, ESJ, 2016)
Nowadays, substantial changes have taken place in work reality, having a considerable impact on the career management prospects. Scenarios such as restructuring, delayering, downsizing of the business organizations, alongside the technological developments have inevitably affected the career management reality. The twenty first century career is no longer a linear process, confined to the organization’s borders, the individuals are taking command, and the required approach is to be more flexible and adaptive in order to develop the indispensable skills and knowledge to meet the aimed goals (Hall, 1996). Discussing in terms of having an everlasting career is becoming irrelevant, instead finding opportunities to improve the professional expertise and life-long learning, is an issue of concern for the career management prospects from both perspectives. The organization is no more concerned, in a selfless and/or patriarchal sense, for the future development of its employees. The competencies are the only safe channels into sustaining marketability and employability in the fluctuant labor market. Career management is a highly delicate subject in need of special care accordingly; as the individual targets not only material gratification, but also spiritual replenishment, meanwhile the organizations aim at gaining competitive advantage in this rapidly changing work environment. The paper will delve upon some of the most conspicuous theoretical career management approaches with regard to the organizational and the individual spectrums, identifying the respective new developments, vital not only to the professionals but to the practitioners interested in the issue and those who wish to harvest another updated perspective on the subject matter.